Injuries leading to hospitalisation in the first year of life: analysis by trimester of age using coded data and textual description - Victor Siskind; Debbie Scott (Australian and New Zealand Journal of Public Health, 2013)
Abstract Objective: To describe unintentional injuries to children aged less than one year, using coded and textual information, in three‐month age bands to reflect their development over the year. Methods: Data from the Queensland Injury Surveillance Unit was used. The Unit collects demographic, clinical and circumstantial details about injured persons presenting to selected emergency departments across the State. Only injuries coded as unintentional in children admitted to hospital were included for this analysis. Results: After editing, 1,082 children remained for analysis, 24 with transport‐related injuries. Falls were the most common injury, but becoming proportionately less over the year, whereas burns and scalds and foreign body injuries increased. The proportion of injuries due to contact with persons or objects varied little, but poisonings were relatively more common in the first and fourth three‐month periods. Descriptions indicated that family members were somehow causally involved in 16% of injuries. Our findings are in qualitative agreement with comparable previous studies. Conclusion: The pattern of injuries varies over the first year of life and is clearly linked to the child's increasing mobility. Implications: Injury patterns in the first year of life should be reported over shorter intervals. Preventive measures for young children need to be designed with their rapidly changing developmental stage in mind, using a variety of strategies, one of which could be opportunistic developmentally specific education of parents.